Treatment of Guaranteed Indebtedness Allowed in Airport Transportation Infrastructure Concession Contracts - Elías Naranjo, Silvana Patricia (2015)
Taking in account the need of financing of inversions to be done by the concessionaires on the frame of concession contracts, this article develops the treatment of Guaranteed Indebtedness Allowed in the concession contracts on airport matter, which general concepts are also applicable to other types of public use transport infrastructure. In this way, the concept of Creditor Allowed is explained, and the guarantees that can be given in the frame of the referred Indebtedness are analyzed, making a comparison of these concepts in the different concession contracts.